2009
DOI: 10.1152/ajpendo.90770.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of type I interferons on IGF-mediated autocrine/paracrine growth of human neuroendocrine tumor cells

Abstract: We recently demonstrated that interferon (IFN)-β has a more potent antitumor activity than IFN-α in BON cells, a neuroendocrine tumor (NET) cell line. The present study showed the role of type I IFNs in the modulation of the insulin-like growth factor (IGF) system in NETs. BON cells expressed IGF-I, IGF-II, IGF-I receptor, and insulin receptor mRNA. In addition, IGF-I and IGF-II stimulated the proliferation of BON cells and induced an inhibition of DNA fragmentation (apoptosis). As evaluated by quantitative RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
(42 reference statements)
0
22
0
Order By: Relevance
“…9 The same authors also demonstrated the synergistic antiproliferative activity of combined IFN-b and troglitazone treatment on pancreatic cancer cell lines 10 and the antitumor activity of IFNb in human neuroendocrine cancer cells, mainly counteracting the IGF-II autocrine/paracrine growth loop. 11 The current development of cancer immunotherapy and the relative success of immune-check point inhibitors such as Ipilimumab (anti-CTLA-4) and Nivolumab/Pembrolizumab (anti-PD-1) in the treatment of different malignancies has prompted the design of multiple studies aimed to test this kind of treatment also in PC patients. 1,12,13 At this aim, it has already been shown that PC cells can be recognized and killed by activated cytotoxic T lymphocyte (CTL) precursors sensitized to recognize PTHrP-or PSA-derived epitopes in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…9 The same authors also demonstrated the synergistic antiproliferative activity of combined IFN-b and troglitazone treatment on pancreatic cancer cell lines 10 and the antitumor activity of IFNb in human neuroendocrine cancer cells, mainly counteracting the IGF-II autocrine/paracrine growth loop. 11 The current development of cancer immunotherapy and the relative success of immune-check point inhibitors such as Ipilimumab (anti-CTLA-4) and Nivolumab/Pembrolizumab (anti-PD-1) in the treatment of different malignancies has prompted the design of multiple studies aimed to test this kind of treatment also in PC patients. 1,12,13 At this aim, it has already been shown that PC cells can be recognized and killed by activated cytotoxic T lymphocyte (CTL) precursors sensitized to recognize PTHrP-or PSA-derived epitopes in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two cores from different areas approaches for novel treatment strategies, even if the literature characterizes better the role of these markers in neuroendocrine tumors rather than squamous. [53][54][55][56] However, detailed studies will be required for better understanding of the complex mechanism of carcinogenesis relating to OSCCs and to improve chemoradiotherapy through the discovery of new therapeutic markers. Our data lead support to the need of detecting the expression of EGFR and its phosphorylated isoforms in clinical practice and diagnostic management of OSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this increase and the reciprocal effect between IGF and IGF-R may be an attempt to regulate the cellular metabolism and the cellular glucose transport (Zoidis et al, 2011). These IGF actions can have also relation with autocrine, paracrine, and with endocrine regulatory mechanisms in different tissues (Pavelić et al, 2007;Vitale et al, 2009). Likewise, also the salivary glands are dependent on factors of growth and endocrine, autocrine, and paracrine signals, which regulate the cell division, apoptosis, and histodifferentiation (Jaskoll and Melnick, 1999).…”
Section: Discussionmentioning
confidence: 99%